Abi Azkakia’s Da’wah Through Mobile Legends in Structuration Perspective: Da’wah Abi Azkakia Melalui Mobile Legends dalam Perspektif Strukturasi - Perdana, Wahyu Ilham; Dharma, Ferry Adhi (House of Wisdom: Journal on Library and Information Sciences, 2025)
Background: The rapid growth of digital platforms has created new opportunities for Islamic preaching (da’wah), including within online gaming communities. Specific Background: Mobile Legends, a widely played mobile game, presents a unique arena where religious messages can intersect with popular gamer culture. Knowledge Gap: While digital da’wah via social media is well-documented, limited research explores its practice within online game live-streaming through the lens of Anthony Giddens’ structuration theory. Aims: This study examines Ustadz Abi Azkakia’s strategies in delivering Islamic values through Mobile Legends live-streaming on TikTok, interpreting interactions between agents and structures. Results: Using autoethnography and participant interviews, findings reveal that Ustadz Abi integrates religious symbols (e.g., peci) and gamer-adapted communication styles to embed tauhid, qada and qadar, and Islamic ethics into gameplay. His approach has been generally well-received, though some players report distraction from the gaming experience. He has established legitimacy and positive influence within the Mobile Legends community. Novelty: This study offers an original perspective on structuration in digital da’wah by showing how a religious figure reshapes online gaming spaces into moral discourse arenas. Implications: Insights highlight the potential and challenges of integrating religious outreach into entertainment-driven digital environments. Highlights: Integrates Islamic values into popular online gaming culture. Uses Giddens’ structuration to interpret agent–structure interaction. Balances entertainment with religious message delivery. Keywords: Digital Da’wah, Online Games, Mobile Legends, Structuration Theory, Autoethnography